Experimental Study on the Compaction and Deformation of Filling Gangue by Reducing Waste Gangue for Filling Mining - Dong, Yue; Zhang, Xinguo; Lin, Jia; Zhao, Jinhai; Meng, Zixuan (Frontiers in Materials, 2021)
The coal mining technology of fully mechanized solid filling is an efficient and green mining method that integrates "sediment reduction" and "emission reduction". However, the discharge of wasted gangue and surface subsidence are controlled by the amount of wasted gangue used in filling mining and the compaction rate of the gangue filled into a goaf, respectively. To increase the consumption of wasted gangue and reduce surface subsidence, mixed gangue composed of equal-quality washed gangue and crushed gangue is proposed as a raw material for solid filling on the basis of gradation theory. Next, a screening experiment was performed to analyze the grain gradation of different specimens, and a compression experiment was executed to compare and analyze the compression characteristics. The results show that the nonuniformity coefficient of mixed gangue is 55.2 and the curvature coefficient is 1.53, which significantly improves the grain gradation of washed gangue. The degree of relative compaction of mixed gangue is 1.226, which is significantly lower than that of washed gangue, which is 1.33. The deformation modulus of the mixed gangue is 23~135 MPa, which is better than that of washed gangue (26~100 MPa), indicating that the compressive resistance of the mixed gangue is significantly improved. The case study of the Tangkou mine suggests that mixed gangue greatly promotes the consumption of wasted gangue and can effectively control the surface deformation.